Atomic structure evolution of high entropy metallic glass microwires at cryogenic temperature. (1st April 2019) - Yin, Hangboce; Huang, Yongjiang; Daisenberg, Dominik; Xue, Peng; Jiang, Songshan; Ru, Weinan; Jiang, Sida; Bao, Ying; Bian, Xilei; Tong, Xing; Shen, Hongxian; Sun, Jianfei
Abstract: The atomic structure evolution of Gd36 Tb20 Co20 Al24 high entropy metallic glass microwire from room to cryogenic temperature has been studied by in-situ high energy synchrotron X-ray diffraction. During the cooling process, the atomic volume decreases. For short-range order, the coordination numbers of all atomic pairs increase. As the temperature decreases, bond lengths of large atom-small atom and small atom-small atom pairs keep decreasing whereas that of large atom-large atom pairs unexpectedly increases continuously. The mechanism of atomic structure evolution is proposed, which might be helpful for better understanding the low temperature magnetocaloric effect of high entropy metallic glasses. Graphical abstract: Unlabelled Image